Willingness to utilize cervical cancer screening among Ethiopian women aged 30–65 years - Desta, Adugna Alemu; Alemu, Fikadu Tolesa; Gudeta, Moges Beya; Dirirsa, Dejene Edosa; Kebede, Andualem Gezahegn (Frontiers in Global Women's Health, 2022)
Background Cervical cancer screening is a means of detecting cervical cancer early, before it develops, in order to reduce disease mortality and morbidity. When women are screened for cervical cancer between the ages of 30 and 40 years at least one time in their life, their risk of cancer could be decreased by 25–36%. Despite this advantage, cervical cancer screening coverage in Ethiopia is still <2%. As a result, we wanted to see how ready women in the Girar Jarso district, Ethiopia, were to get a cervical cancer test. Methodology Community-based cross-sectional study was done using a stratified cluster sampling technique among 855 women aged 30–65 years in the Girar Jarso district, Ethiopia, from 1 June 2021 to 1 September 2021. A pretested and semi-structured interviewer-administered questionnaire was used to collect the data. EpiData management version 4.6 was used to enter data, which was then exported to SPSS version 23 for analysis. Logistic regression analysis was performed, and variables with a p-value of <0.05 were taken as statistically significant predictors of the willingness to utilize cervical cancer screening. Results Of the 855 women, only 315 (46.7%, CI = 43–50.3) women were willing to be checked for cervical cancer, with 181 (21.2%) women having been screened at least one time in their life. Age of 30–39 years [AOR = 2.80 (95% CI: 1.05, 7.48)], urban resident [AOR = 2.12 (95% CI: 1.06, 4.48)], positive attitude [AOR = 1.68 (95% CI: 1.11, 2.53)], wealth status, awareness of cervical cancer, and low perceived barriers were independent predictors of the willingness to utilize cervical cancer screening. Conclusion and recommendation The willingness to utilize cervical cancer screening services is low in the Girar Jarso district. To improve community awareness and attitude, continued and sustainable advocacy on the value of cervical cancer screening should be offered through mass media and health extension workers.